41‐5: Invited Paper: Quantum Dot Conversion Layers Through Inkjet Printing. Issue 1 (30th May 2018) - Lee, Ernest; Tangirala, Ravi; Smith, Austin; Carpenter, Amanda; Hotz, Charlie; Kim, Heejae; Yurek, Jeff; Miki, Takayuki; Yoshihara, Sunao; Kizaki, Takeo; Ishizuka, Aya; Kiyoto, Ikuro
Abstract : Quantum dot color conversion layers have the potential to greatly improve the efficiency and color performance of displays including and beyond liquid crystal displays. To fully realize these improvements, the quantum dots must be deposited and patterned at high resolution. One promising method for achieving this is through inkjet printing. In this paper we report on the fabrication and characterization of quantum dot inks, as well as films made from inkjet deposition of these materials.